A method for preparing a fully crystalline mor molecular sieve
Patent Information
- Application Number
- CN202410310893.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-19
AI Technical Summary
The addition of inert binders to existing MOR molecular sieve catalysts leads to dilution of active centers, pore blockage, and decreased diffusion performance, affecting catalyst stability and mechanical strength, making it difficult to meet the requirements of industrial applications.
A binder-free, fully crystalline MOR molecular sieve preparation method was adopted. By controlling the suspension forming and crystallization reaction, a high-crystallinity, high-strength MOR molecular sieve catalyst was prepared. The method includes drying, forming, calcination and ammonium ion exchange steps, avoiding the use of binders.
The prepared fully crystalline MOR molecular sieve catalyst has high specific surface area, good mechanical strength and diffusion properties, making it suitable for industrial applications. Moreover, the synthesis process is simple, has a short cycle, produces little waste, and has significant economic benefits.
Abstract
Description
Technical Field
[0001] This invention relates to a fully crystalline catalyst, specifically a method for preparing a fully crystalline MOR molecular sieve. Background Technology
[0002] The synthesis of mordenite (MOR) has a history of over 70 years. Due to its high silicon content and stable framework, mordenite can withstand certain levels of acid and heat treatment. As a high-performance catalyst, mordenite is widely used in catalytic cracking, isomerization of n-alkanes, cycloalkanes, and aromatics, alkylation, disproportionation and alkyl transfer, reforming, dewaxing and pour point depressing, methanol oxidation, and other petrochemical processes. Furthermore, it shows promising applications in fine chemicals, agriculture, building materials, and environmental protection. Catalyst powders, due to their small particle size, are inconvenient to use in practical applications, exhibiting weaknesses such as difficulty in recovery, easy deactivation, and aggregation. Therefore, pre-forming is necessary. During the forming process, binders are generally added, typically comprising 10-40% or even higher of the total catalyst weight. This gives the catalyst a specific shape and mechanical strength, making binders essential. Existing industrial MOR molecular sieve catalysts contain large amounts of binders; however, binders are generally inert components, and their addition effectively "dilutes" the active centers of the molecular sieve, increasing the actual reaction space velocity and accelerating catalyst deactivation. Furthermore, binders can block pores in the molecular sieve, affecting diffusion performance and ultimately leading to poor catalyst stability. Fully crystalline molecular sieves, on the other hand, refer to zeolite particles that do not contain inert binders. Essentially, the binder added during the molecular sieve forming process is converted into an effective component of the molecular sieve. They exhibit high crystallinity, a larger usable effective surface area, and better catalytic performance. Simultaneously, they possess good mechanical strength, making them perfectly suited for industrial applications. Therefore, research on fully crystalline zeolite molecular sieves has significant industrial application value. Summary of the Invention
[0003] To address the above-mentioned problems, this invention provides a simple method for preparing fully crystalline MOR molecular sieves.
[0004] To achieve the above-mentioned objectives of the present invention, the present invention adopts the following technical solution: This invention provides a fully crystalline MOR molecular sieve catalyst, characterized in that: a method for preparing the fully crystalline MOR molecular sieve catalyst involves sequentially adding an alkali source, an aluminum source, and a silicon source to water, and then sequentially drying, molding, and calcining the resulting suspension to obtain catalyst precursor II; Catalyst precursor II was added to water and crystallized at 150-200 °C for 20-80 hours to obtain catalyst precursor III; The catalyst precursor III was subjected to ammonium ion exchange, washing, drying, and calcination to obtain the fully crystalline MOR molecular sieve catalyst.
[0005] Furthermore, in the above technical solution, in the suspension, the molar ratio of each component, calculated as oxides, is: SiO2 / Al2O3 = 10~35, OH... - / SiO2=0.05~0.20, H2O / SiO2=5~15.
[0006] Furthermore, in the above technical solution, the alkali is at least one of NaOH and potassium hydroxide; the silicon source is at least one of water glass, silica sol, type C silica gel, fumed silica, TEOS, and TMOS; and the aluminum source is at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum sol, and aluminum isopropoxide.
[0007] Furthermore, in the above technical solution, the suspension is dried and shaped into at least one of the following: strip, sphere, clover, cylindrical with a central hole, four-leaf clover, dumbbell, honeycomb, wheel, or cross-shaped column.
[0008] Furthermore, in the above technical solution, after the suspension is dried and shaped, it is calcined at 100℃~650℃ for 0~8h to obtain catalyst precursor II.
[0009] Furthermore, in the above technical solution, in the crystallization reaction, the mass ratio of catalyst precursor II to water is 1:3~20.
[0010] Furthermore, in the above technical solution, the ammonium salt used for the catalyst precursor III ammonium ion exchange is at least one of ammonium nitrate, ammonium chloride, ammonium sulfate, and ammonium carbonate.
[0011] Furthermore, in the above technical solution, the exchange temperature of the catalyst precursor III ammonium ion exchange is 40℃~90℃, and the ammonium salt concentration is 3~10wt%.
[0012] Furthermore, in the above technical solution, catalyst precursor III is subjected to ammonium ion exchange, washing, and drying, and then calcined at 450℃~650℃ for 4~8 h to obtain the fully crystalline MOR molecular sieve catalyst.
[0013] This invention provides a specific method for preparing a fully crystalline MOR molecular sieve catalyst, comprising the following steps: a) Weigh a certain amount of alkali to prepare solution A, then weigh a certain amount of aluminum source and add it to solution A. Stir until the aluminum source dissolves. At room temperature, add a certain amount of silicon source to solution A and stir at room temperature for 2-24 hours. Set aside the resulting suspension. b) Transfer the above suspension to an oven at 80~150℃ and dry it to the required dry base for molding. Then, mold it according to the requirements, let it dry at room temperature, and then transfer it to an oven at 100~150℃ for 6~12 hours. Then, calcine it at a certain temperature for a certain time to obtain catalyst precursor II. c) Catalyst precursor II is placed in deionized water containing a certain proportion and crystallized at 150~200℃ for 20~80 hours to obtain fully crystalline catalyst precursor III; d) Catalyst precursor III is exchanged with 3-10 wt% ammonium salt aqueous solution at 40-90 °C, washed and dried, and then calcined at 450-650 °C for 4-8 hours to obtain the desired fully crystalline MOR molecular sieve catalyst.
[0014] The beneficial effects of this invention are as follows: This invention provides a method for preparing a fully crystalline MOR molecular sieve catalyst. This method involves first drying and shaping a prepared raw material suspension, followed by a crystallization reaction. MOR molecular sieve catalysts shaped into specific forms can be obtained without the addition of additional binders and templates. Furthermore, the fully crystalline MOR molecular sieve catalyst prepared by this method has a specific surface area of 400-550 m². 2 / g, pore volume 0.18~0.30 cm³ 3 The radial average crushing strength of the formed strip-shaped fully crystalline MOR molecular sieve catalyst is 50~150 N; the point crushing strength of the formed spherical fully crystalline MOR molecular sieve catalyst with a diameter of 3~6 mm is 30~85 N; and the wear of the formed spherical fully crystalline MOR molecular sieve catalyst with a diameter of 40~150 μm is <3.0%. The MOR molecular sieve prepared by this invention has high crystallinity, high strength, a simple synthesis process, short synthesis cycle, low waste, and significant economic benefits. It can be applied to large-scale factory production and has great application value. Detailed Implementation
[0015] The silica sol used in this embodiment contains 30% silica, and the sodium aluminate used contains 51.87% Al2O3 and 40.17% Na2O by mass. Example 1
[0016] a) Weigh 2.0 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 4.5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Set aside the resulting suspension. b) The above suspension was transferred to an oven at 80 °C and dried to 85% dry basis. Then it was extruded into clover shape (3 mm in diameter), placed at room temperature to dry, and then transferred to an oven at 120 °C to continue drying for 12 hours. Finally, it was calcined at 450 °C for 4 hours to obtain catalyst precursor II. c) Place 10 g of catalyst precursor II in a stainless steel reactor with a polytetrafluoroethylene liner containing 100 g of deionized water, and crystallize it at 170 °C for 40 hours to obtain fully crystalline catalyst precursor III. d) Catalyst precursor III was exchanged with a 5 wt% ammonium nitrate aqueous solution at 50 °C, washed, dried, and then calcined at 650 °C for 4 hours to obtain the desired fully crystalline MOR molecular sieve catalyst with a specific surface area of 450 m². 2 / g, pore volume 0.24 cm 3 / g, with a radial average crushing strength of 100 N. Example 2
[0017] a) Weigh 2.0 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 3.17 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Set aside the resulting suspension. b) The above suspension was transferred to an oven at 85 °C and dried to 85% dry basis. Then it was extruded into a clover shape (3 mm in diameter), placed at room temperature to dry, and then transferred to an oven at 110 °C to continue drying for 14 hours. Then it was calcined at 350 °C for 5 hours to obtain catalyst precursor II. c) Place 10 g of catalyst precursor II in a stainless steel reactor with a polytetrafluoroethylene liner containing 50 g of deionized water, and crystallize it at 180 °C for 35 hours to obtain fully crystalline catalyst precursor III. d) Catalyst precursor III was exchanged with an 8 wt% ammonium nitrate aqueous solution at 60 °C. After washing and drying, it was calcined at 650 °C for 4 hours to obtain the desired fully crystalline MOR molecular sieve catalyst with a specific surface area of 420 m². 2 / g, pore volume 0.21 cm³ 3 / g, with a radial average crushing strength of 60 N. Example 3
[0018] a) Weigh 2.0 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Set aside the resulting suspension. b) The above suspension was transferred to an oven at 90 °C and dried to 85% dry basis. Then it was extruded into strips (6 mm in diameter), placed at room temperature to dry, and then transferred to an oven at 120 °C to continue drying for 12 hours. Then it was calcined at 550 °C for 3 hours to obtain catalyst precursor II. c) Place 10 g of catalyst precursor II in a stainless steel reactor with a polytetrafluoroethylene liner containing 150 g of deionized water, and crystallize it at 190 °C for 30 hours to obtain fully crystalline catalyst precursor III. d) Catalyst precursor III was exchanged with a 7wt% ammonium nitrate aqueous solution at 80 °C. After the exchange, it was washed, dried, and calcined at 650 °C for 4 hours to obtain the desired all-crystalline MOR molecular sieve catalyst with a specific surface area of 520 m². 2 / g, pore volume 0.27 cm³ 3 / g, with a radial average crushing strength of 130 N. Example 4
[0019] a) Weigh 2.3 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 4.5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Set aside the resulting suspension. b) The above suspension was transferred to an oven at 80 °C and dried to 45% dry basis. Then it was sprayed into spherical shape (particle size distribution 40-150 micrometers), placed at room temperature to dry, and then transferred to an oven at 100 °C to continue drying for 12 hours. Then it was calcined at 450 °C for 4 hours to obtain catalyst precursor II. c) Place 10 g of catalyst precursor II in a stainless steel reactor with a polytetrafluoroethylene liner containing 40 g of deionized water, and crystallize it at 200 °C for 20 hours to obtain fully crystalline catalyst precursor III. d) Catalyst precursor III was exchanged with a 5 wt% ammonium nitrate aqueous solution at 50 °C, washed, dried, and then calcined at 500 °C for 6 hours to obtain the desired fully crystalline MOR molecular sieve catalyst with a specific surface area of 410 m². 2 / g, pore volume 0.22 cm³ 3 / g, particle abrasion rate is 0.9%. Example 5
[0020] a) Weigh 1.5 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 4.5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Set aside the resulting suspension. b) The above suspension was transferred to an oven at 80 °C and dried to 45% dry basis. Then it was sprayed into spherical shape (particle size distribution 40-150 micrometers), placed at room temperature to dry, and then transferred to an oven at 120 °C to continue drying for 12 hours. Finally, it was calcined at 450 °C for 4 hours to obtain catalyst precursor II. c) Place 10 g of catalyst precursor II in a stainless steel reactor with a polytetrafluoroethylene liner containing 100 g of deionized water, and crystallize it at 170 °C for 40 hours to obtain fully crystalline catalyst precursor III. d) Catalyst precursor III was exchanged with a 10 wt% ammonium nitrate aqueous solution at 40 °C, washed, dried, and then calcined at 650 °C for 4 hours to obtain the desired fully crystalline MOR molecular sieve catalyst with a specific surface area of 400 m². 2 / g, pore volume 0.19 cm 3 / g, with a particle wear rate of 1.1%.
[0021] Comparative Example 1 a) Weigh 2.0 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 4.5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Add the resulting suspension to a stainless steel reactor with a polytetrafluoroethylene liner. After crystallization reaction at 170 °C for 40 hours, calcine at 450 °C for 4 h to obtain MOR molecular sieve. b) Mix 20 g of the obtained MOR molecular sieve with 2.22 g of 30% silica sol, then extrude it into a clover shape (3 mm in diameter), let it dry at room temperature, then transfer it to a 120℃ oven to continue drying for 12 hours, and then calcine it at 450℃ for 4 hours to obtain the shaped MOR molecular sieve. c) The formed MOR molecular sieve was exchanged with a 5wt% ammonium nitrate aqueous solution at 50 °C, washed, dried, and then calcined at 650 °C for 4 hours to obtain a clover-shaped MOR molecular sieve catalyst with a specific surface area of 400 m². 2 / g, pore volume 0.18cm 3 / g, with a radial average crushing strength of 45 N.
[0022] Comparative Example 2 a) Weigh 2.0 g NaOH and add it to 8 g deionized water to prepare solution A. Then weigh 4.5 g sodium aluminate and add it to solution A. Stir until dissolved. At room temperature, add 113 g silica sol to solution A and stir at room temperature for 2 h. Add the resulting suspension to a stainless steel reactor with a polytetrafluoroethylene liner. After crystallization reaction at 170 °C for 40 hours, calcine at 450 °C for 4 h to obtain MOR molecular sieve. b) Mix 20 g of the obtained MOR molecular sieve with 4 g of 30% silica sol, then extrude it into a clover shape (3 mm in diameter), let it dry at room temperature, then transfer it to a 120℃ oven to continue drying for 12 hours, and then calcine it at 450℃ for 4 hours to obtain the shaped MOR molecular sieve. c) The formed MOR molecular sieve was exchanged with a 5wt% ammonium nitrate aqueous solution at 50 °C, washed, dried, and then calcined at 650 °C for 4 hours to obtain a clover-shaped MOR molecular sieve catalyst with a specific surface area of 380 m². 2 / g, pore volume 0.15cm 3 / g, radial average crushing strength is 40 N The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a fully crystalline MOR molecular sieve catalyst, characterized in that: The alkali source, aluminum source and silicon source were added to water in sequence, and the resulting suspension was dried, shaped and calcined to obtain catalyst precursor II. Catalyst precursor II was added to water and crystallized at 150-200℃ for 20-80 hours to obtain catalyst precursor III; The catalyst precursor III was subjected to ammonium ion exchange, washing, drying, and calcination to obtain the fully crystalline MOR molecular sieve catalyst described above. In the suspension, the molar ratio of aluminum source and silicon source (based on oxides) is SiO2 / Al2O3 = 10~35, and OH... - / SiO2=0.05~0.20, H2O / SiO2=5~15; The mass ratio of catalyst precursor II to water is 1:3~20.
2. The preparation method according to claim 1, characterized in that: The suspension, after drying, is shaped into at least one of the following: strip, sphere, clover, cylindrical with central hole, four-leaf clover, dumbbell, honeycomb, wheel, and cross-shaped column.
3. The preparation method according to claim 1 or 2, characterized in that: The exchange temperature of the ammonium ion exchange process is 40℃~90℃, and the ammonium salt used is at least one of ammonium nitrate, ammonium chloride, ammonium sulfate, and ammonium carbonate, with a concentration of 3~10wt%.
4. The preparation method according to claim 1 or 2, characterized in that: The alkaline source is at least one of sodium hydroxide and potassium hydroxide; The silicon source is at least one of water glass, silica sol, type C silica gel, fumed silica, TEOS, and TMOS. The aluminum source is at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum sol, and aluminum isopropoxide.
5. The preparation method according to claim 1 or 2, characterized in that: The suspension was dried and shaped in sequence, and then calcined at 350℃~650℃ for 3~8h to obtain catalyst precursor II.
6. The preparation method according to claim 1 or 2, characterized in that: In step d, catalyst precursor III is subjected to ammonium ion exchange, washing, and drying in sequence, and then calcined at 450℃~650℃ for 4~8h to obtain the fully crystalline MOR molecular sieve catalyst.
Citation Information
Patent Citations
Preparation method of binder-free mordenite catalyst
CN102039152A
Preparation method of non-binder titaniferous mercerizing molecular sieve catalyst
CN103252252A
